The effects of watermelon and Tualang honey based energy drinks on postprandial antioxidant activity and oxidative stress in male collegiate athletes: a dose-response and time-course efficacy study - Rohit Chaudhary,; Hamzah, Sareena Hanim; Azlina Abdul Aziz,; Zulkarnain Jaafar,; Nik Shanita Safii, (Progress in Nutrition, 2022)
Background: Exogenous antioxidant supplementation via natural food sources may enhance antioxidant activity and reduce oxidative stress. This study examined the dose-response and time-course effect of watermelon and Tualang honey based energy drinks (WED) on postprandial antioxidant activity and oxidative stress in male collegiate athletes.Methods: This randomized, two-dose, crossover design study included 12 healthy male collegiate athletes. Participants consumed WED of 0.5 g CHO/kg (WML) or 1g CHO/kg (WMH) on two occasions separated by 7 days washout period. The primary outcome ferric reducing antioxidant power (FRAP) and secondary outcomes total phenolic content (TPC), reactive oxygen species (ROS) and malondialdehyde (MDA) were analyzed in blood samples drawn at baseline (fasting) and at 30, 60, 90, 120 minutes post-ingestion of WED’s.Results: The area under the curve for FRAP (AUCFRAP) and ROS (AUCROS) was higher (p = 0.024) and lower (p = 0.021) respectively in WMH compared to WML trial. AUCTPC was higher (p = 0.001) in WML, whereas, AUCMDA showed no significant difference (p ˃ 0.05) between both trials. Concentrations of ROS and MDA in plasma significantly decreased (p < 0.05) from baseline to 60 min post-consumption of WMH. Plasma FRAP concentration peaked (p ˃ 0.05) at 60 min post ingestion of WMH, whilst it showed constant decline post consumption of WML. Plasma TPC concentration peaked (p < 0.05) at 60 min in WML, whereas it increased (p ˃ 0.05) over time in WMH trial.Conclusions: WMH demonstrated an optimal increment in antioxidant activity and a decrease in oxidative stress at 60 min after its ingestion among male collegiate athletes.